Lactate-driven macrophage polarization in the inflammatory microenvironment alleviates intestinal inflammation - Zhou, Hai-Cun; Yu, Wen-Wen; Yan, Xin-Yan; Liang, Xiao-Qin; Ma, Xiu-Feng; Long, Jian-Ping; Du, Xiao-Yan; Mao, Hong-Yan; Liu, Hong-Bin (Frontiers in Immunology, 2022)
Background Lactate has long been considered an intermediate by-product of glucose metabolism. However, in recent years, accumulating evidence reveals that lactate has unique biological activities. In previous studies, lactate signaling was shown to inhibit inflammation. Furthermore, in vitro experiments have shown that lactate can promote the transformation of pro-inflammatory macrophages into anti-inflammatory macrophages. However, no in vivo studies have shown whether lactate can alleviate inflammation. Methods RAW 264.7 macrophages were stimulated by LPS to induce an M1 phenotype, and cultured with low and high concentrations of lactate. The cells were then observed for phenotypic transformations and expression of inflammatory mediators and surface markers. The expression of inflammatory factors was also analyzed in the cell-free supernatant fraction. Further, a mouse model of DSS-induced colitis was established and treated with lactate. Colonic tissue injury was monitored by histopathological examinations. Results The in vitro experiments showed that lactate promoted the transformation of activated macrophages to M2 phenotype and decreased the expression of TLR4-mediated NF-κB signaling proteins and inflammatory factors. In the DSS-induced colitis mouse model, lactate promoted the phenotypic transformation of macrophages in colonic tissue, reduced inflammation and organ damage, inhibited the activation of TLR4/NF-κB signaling pathway, decreased the serum levels of pro-inflammatory factors, increased the expression of anti-inflammatory factors, promoted the repair of the intestinal mucosal barrier and reduced the severity of colitis. Conclusions Lactate inhibits the TLR/NF-κB signaling pathway and the production of pro-inflammatory factors by promoting polarization of macrophages. In addition, lactate promotesthe repair of the intestinal mucosal barrier and protects intestinal tissue in inflammation. Furthermore, lactate is relatively safe. Therefore, lactate is a promising and effective drug for treating inflammation through immunometabolism regulation.